Synergistic effect of binary ligands on nucleation and growth/size effect of nanocrystals: Studies on reusability of the solvent. Issue 14 (4th August 2014) - H.R., Chandan; V., Saravanan; Krishna Pai, Ranjith; Geetha Balakrishna, R.
Abstract